PERENCANAAN KEBUTUHAN TENAGA REKAM MEDIS DI PUSKESMAS KENDALKEREP - Hariez, Tsalits Maulidah (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
Workload is one important component in calculating the workforce requirements, that’s means the amount of workforce needed tailored to the exiting workload. Workload Indicators of Staffing Need (WISN) is a method to calculating workforce requirements based on real workload undertaken by workforce. There are currently 2 medical record personnel with D3 graduates of Medical Record and Health Information and 3 with high school graduates. The planning of medical record personnel needs has not yet been made so that the policies in the planning of personnel needs in the medical record department are still unclear. Besides that there are also medical record officers who also double as registration officers and coding officers. This study aims to determine the amount of medical record human resources needed at the Kendalkerep Health Center using the WISN method. With a non-experimental descriptive research design conducted by observation and interview, the results of the study show that the calculation of the WISN method takes into account the available work time factors, work units to be calculated, workload standards, allowance standards and the amount of power calculated. From the results of the study, there were 91,392 minutes / year available work time, standard workload of 7,550,419 minutes / year, allowance time of 0.27 and then the human resource needs in the medical record unit were 6 workers. The conclusion is Kendalkerep Health Center needs to add 1 medical record personnel to overcome the problem.